Buy Now, Pay Later Services: Adoption Drivers among Digitally Fluent Generations in Sarawak - Tang, Maximus Balla; Sa'adi, Nurzalikha; Andam, Jessica Lyn (Journal of Technology Management and Business, 2025)
In the ever-evolving landscape of consumer finance, Buy Now Pay Later (BNPL) has emerged as a transformative payment solution. BNPL effectively bridges the gap between traditional credit and debit methods by offering a middle ground that combines the benefits of both. The study aims to identify the adoption factor of BNPL among Generation Y (Gen Y) and Z (Gen Z) in Sarawak. Sarawak is undergoing fierce digital transformation through Sarawak Digital Transformation Blueprint 2030. BNPL plays a significant role by supporting consumer spending and empowering local businesses to thrive in the digital economy. This paper adapts and expands the Unified Theory of Acceptance and Use of Technology (UTAUT) in addressing the adoption factors of BNPL among Gen Y and Z in Sarawak. The theoretical framework has been expanded to include other variables like perceived security and attitude to broaden the usage of UTAUT in the BNPL field. Data were collected from 384 respondents and examined using SmartPLS 4.0 software. The findings indicated that performance expectancy, effort expectancy, attitude and perceived security were significant in the adoption of BNPL services among Gen Y and Z in Sarawak. As a result of the study, research has added value to the existing literature and contributed an expanded model of UTAUT for future researchers and academicians to adopt in conducting studies regarding financial technology, especially BNPL.